Robust Fault Diagnosis Algorithm for a Class of Nonlinear Systems - Hai-gang Xu; Yue-feng Liao; Xiao Han (Journal of Control Science and Engineering)
A kind of robust fault diagnosis algorithm to Lipschitz nonlinear system is proposed. The novel disturbances constraint condition of the nonlinear system is derived by group algebra method, and the novel constraint condition can meet the system stability performance. Besides, the defined robust performance index of fault diagnosis observer guarantees the robust. Finally, the effectiveness of the algorithm proposed is proved in the simulations.